Head circumference in Iranian infants - Mohammad Esmaeili; Marjan Esmaeili; Reza saeidi; fateme ghane shabaf (Mashhad University of Medical Sciences, 2015)
Introduction: Head circumference (HC) measurement is one of the important parameter for diagnosis of neurological, developmental disorders and dysmorphic syndromes. Recognition of different disorders requires an understanding of normal variation for HC size, in particular, in infancy period with most rapid growth of the brain. Because of international and interracial standard chart differences about anthropometric indices, some differences from local to local, generation to generation and changes in ethnic mix of population and socioeconomic factors, periodic revolution of HC size is suggested. The aims of our study were presenting local HC standard for an Iranian infant population and comparison with the American national center of health statistics (NCHS) charts accepted by WHO. Methods: 1003 subjects aged from birth to 24 months apparently healthy normal children enrolled randomly in this cross sectional study. HC size were measured and recorded. Tables and graphs were depicted by Excel Microsoft Office 2007. We use two tailed t-student test for statistical analysis. Results: The mean of HC size in boys was larger than girls. The curves were followed a similar pattern to NCHS based on a visual comparison. Overall our subjects in both sexes at birth time had smaller HC size than NCHS. In other ages our children had larger HC size than those of NCHS. Conclusion: Because of international and interracial difference of HC size. We recommend in each area of the world, local anthropometric indices are constructed and used clinically. In addition more extensive and longitudinally design comprehensive studies is suggested.